INFLUENCE INFLATION, BI RATE, RATIO PROFIT SHARING, GDP AGAINST MUDHARABAH SAVINGS AT ISLAMIC COMMERCIAL BANKS - Rafika, Lailatul; Wardana, Guntur Kusuma (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Indonesia's economic development at the macro or micro level will affect the performance of BUS in Indonesia. Therefore, BUS must have the ability to adapt to economic developments and pay attention to future prospects. The growth of BUS can be seen from the amount of mudharabah savings deposits. Therefore, knowing the factors that influence mudharabah savings deposits is important. Many factors affect the amount of mudharabah savings deposits, including inflation, the BI rate, profit sharing ratio and GDP. The purpose of this study is to determine the influence of Inflation, BI Rate, Profit Sharing Ratio, GDP on Mudharabah Savings in Islamic Commercial Banks in Indonesia partially and simultaneously. This type of research is quantitative research using a descriptive approach. The data used is panel data with panel data regression analysis tools. Panel data regression testing uses the Eviews 12 software application. Using the Non-Probability Sampling Technique. The population in this study amounted to 13 BUS and a sample of 5 BUS was obtained. The results showed that partially the inflation and BI Rate variables had no significant influence on Mudharabah Savings. As for the variable Profit Sharing Ratio and GDP, it has a significant influence on Mudharabah Savings. Simultaneously (together) the independent variables (inflation, BI Rate, Profit Sharing Ratio and GDP) have a significant influence on Mudharabah Savings.